Unraveling the Seed Dispersal System of an Insular “Ghost” Dragon Tree (Dracaena draco) in the Wild - González-Castro, Aarón; Pérez-Pérez, David; Romero, Javier; Nogales, Manuel (Frontiers in Ecology and Evolution, 2019)
Despite being abundant in urban gardens, the Canary Island dragon tree Dracaena draco is close to extinction in the wild. It tends to produce relatively large fruits, which limits the pool of vertebrates that might disperse its seeds. We aimed to shed light on the seed dispersal system of this plant by studying its fruit size in relation to the feeding behavior of its present dispersers, and to discuss on possible differences with the past dispersal system, when large-sized dispersers were abundant. Besides fruit and seed characterization, we performed experiments on seedling emergence (using the characterized seeds), and field observations of the fruit handling behavior of frugivorous birds. Seed removal by granivores beneath and outside the dragon tree canopies was assessed through a field experiment. An additional seedling emergence experiment tested the effect of pulp removal from around the seed (using seeds contained within the fruits and manually depulped seeds). A feeding experiment was carried out with captive individuals of the Canary endemic white-tailed pigeon Columba junoniae –a large frugivore that occasionally consumes D. draco fruits– to test if its gut treatment influences seed viability. Small fruits produced seeds unable to germinate, while most seedling emergence was recorded only for seeds from large fruits. Our observations suggest that the only passerine species able to swallow large fruits is the medium-size passerine Turdus merula, whereas small passerines tended to pluck the pulp without aiding seed dispersal. Nonetheless, Sylvia atricapilla –the largest among the group of small passerines– occasionally transported fruits away from parent plants to consume the pulp, resulting in seed dispersal without any digestive treatment. This behavior indicates S. atricapilla might be occasionally a legitimate disperser of D. draco, since our experiments suggest that seed transport away from parent trees and pulp removal enhance both post-dispersal seed survival and seedling emergence. Lastly, the pigeons used in the experiment regurgitated mostly viable seeds, suggesting the legitimacy of C. junoniae as seed disperser for D. draco. Therefore, although D. draco likely had more seed dispersers in the past, we identified at least two bird species that can still disperse its seeds nowadays.